Rizogênese in vitro e ex vitro em Peltophorum dubium (Sprengel) Taubert - Curti, Aline Ritter (2014)
Peltophorum dubium is native forest species of Brazil endowed with ecological importance for the recovery of degraded areas and economical for timber purposes. The seeds of this species have low and irregular germination if they are not subjected to treatments to overcome dormancy. However, there are few studies that allow for the vegetative propagation of the species. As a result, the present study aimed to evaluate the formation of roots in shoots of P. dubium applying the techniques of micropropagation and minicutting and acclimatization of plants produced by these techniques. For rooting in vitro micropropagated shoots were subjected to treatments where different culture media were tested, with addition of 30 g L-1 vermiculite, combined with the nutrient media MS, MS/2, WPM, WPM/2 and changes in concentrations of auxin IBA (0, 5, 10 or 20 μM) and sucrose (0, 15 or 30 g L -1) in the presence or absence of agar (0 or 7g L-1) arranged in different tests. The results indicated that the best combination for root formation in vitro shoots of Peltophorum dubium is the use of nutritional WPM/2 without addition of sucrose and auxin, with 7 g L- 1 agar. This condition was still allowing the best performance of the plants during acclimatization in vitro. For rooting of shoots via minicutting, cuttings 3-7 cm apical portion of rooted shoots of seminal origin were used. Root formation after the cuttings are subjected to immersion in solution with 0, 1.000, 2.000 or 4.000 mg L- 1 IBA, from different collections and during 30, 60 or 90 days in a greenhouse with controlled conditions was evaluated for root induction. Rooting in cuttings occurred even without the use of IBA, after successive collections. However, it was increased with the use of up to 2.000 mg L-1 auxin the period of 60 days being sufficient for the formation of roots takes place. The seedlings showed good performance during acclimatization, indicating that the technique is feasible for minicutting plants production Peltophorum dubium.